Synthesis and Antifungal Activity of Some Metal Complexes of 2-(2’-Hydroxybenzylidene)aminophenyl benzimidazole - Garg, Yajula; Kumar Samota, Mahesh; Seth, Gita (Asian Journal of Chemistry, 2016)
Some new metal complexes of 2-(2'-hydroxybenzylidene)aminophenyl benzimidazole (HBAPBI) with Pd(II), Pt(II), Pr(III), Nd(III) VO(II) and UO2(II) have been synthesized. These metal complexes have been characterized on the basis of their elemental analysis, conductance measurement, IR and NMR spectral studies. The metal complexes were found to be more fungitoxic when studied against Alternaria alternata and Aspergillus niger by spore germination inhibition method as compared with dithane M-45, a commercial fungicide.